Employment readiness in adults with intellectual disabilities - Milanović-Dobrota, Biljana; Vidojković, Sara; Japundža-Milisavljević , Mirjana; Đurić-Zdravković , Aleksandra (Specijalna edukacija i rehabilitacija, 2021)
Introduction. Of all people with disabilities, persons with intellectual disabilities are the most numerous unemployed group who wait for a job the longest. In order to spend their day in a more productive way, these people spend time in centres and day-care centres within the system of social protection, but their motivation for work decreases over time. Objectives. The main goal of this research was to determine work readiness in adults with intellectual disabilities by assessing the specific dimension of work motivation, with special emphasis on determining differences in gender, level of formal education, type of family environment, and records in the National Employment Service. Methods. The convenience sample consisted of 78 respondents of both genders, users of services provided by associations for helping persons with intellectual disabilities in Belgrade. Work Readiness Scale (Rose et al., 2010) was used in this research. Results. Adults with intellectual disabilities were moderately interested in employment, but the obtained results differed from the estimated variables. Respondents who were professionally trained for work, as well as those who were registered in the records of the National Employment Service, showed proactive attitudes towards employment. Family support was insufficient and the lack of support was the most pronounced among the respondents living in foster families. No statistically significant differences were found with regard to gender. Conclusion. The obtained results indicate the need to provide professional support to adults with intellectual disabilities regarding the importance of working in integrated employment, with simultaneous cooperation with family members. Also, further research is needed in order to profile work readiness more clearly and adequately plan various services for the inclusion of adults with intellectual disabilities in the world of work.
Keywords: intellectual disabilities; adults; work motivation; employment